(untitled) (Регіональні аспекти розвитку продуктивних сил України, 2017)
The problems of introduction of corporate social responsibility of a bank establishment are investigated in this article. The external social responsibility of the bank is determined here, which includes: sponsorship and charity; participation in state, region and municipality environmental programs; interaction with local authorities; responsibility to society, government, investors, customers, population, competitors and others. The content of the corporate environmental policy is disclosed, including the use of different types of environmental audits, "green supply”, involving employees to the environmental initiatives. The level of social responsibility of the bank is determined by using sociological research of questionnaires bank customers.The priority values of bank are shown, that provide steady development of society, grant of high-quality calculation services, operative decision of financial questions of assistance to professional development of employees.